Hypoxia in tomato (Solanum lycopersicum) fruit during ripening: Biophysical elucidation by a 3D reaction–diffusion model - Xiao, Hui; Verboven, Pieter; Tong, Shuai; Pedersen, Ole; Nicolaï, Bart (Plant physiology (Bethesda), 2024)
Abstract Respiration provides energy, substrates, and precursors to support physiological changes of the fruit during climacteric ripening. A key substrate of respiration is oxygen that needs to be supplied to the fruit in a passive way by gas transfer from the environment. Oxygen gradients may develop within the fruit due to its bulky size and the dense fruit tissues, potentially creating hypoxia that may have a role in the spatial development of ripening. This study presents a 3D reaction–diffusion model using tomato (Solanum lycopersicum) fruit as a test subject, combining the multiscale fruit geometry generated from magnetic resonance imaging and microcomputed tomography with varying respiration kinetics and contrasting boundary resistances obtained through independent experiments. The model predicted low oxygen levels in locular tissue under atmospheric conditions, and the oxygen level was markedly lower upon scar occlusion, aligning with microsensor profiling results. The locular region was in a hypoxic state, leading to its low aerobic respiration with high CO2 accumulation by fermentative respiration, while the rest of the tissues remained well oxygenated. The model further revealed that the hypoxia is caused by a combination of diffusion resistances and respiration rates of the tissue. Collectively, this study reveals the existence of the respiratory gas gradients and its biophysical causes during tomato fruit ripening, providing richer information for future studies on localized endogenous ethylene biosynthesis and fruit ripening.A 3D reaction–diffusion model elucidates the biophysical causes of the internal hypoxia in tomato fruit during ripening.